2018
DOI: 10.1002/anie.201811268
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Addressable Ion Sensing for Real‐Time Monitoring of Extracellular Potassium

Abstract: We report here on al ight addressable potassium (K + )s ensor where light illumination of as emiconducting silicon electrode substrate results in alocalized activation of the faradaic electrochemistry at the illuminated spot. This allows one,b ye lectrochemical control, to oxidize surface bound ferrocene moieties that in turn trigger K + transfer from the overlaid K + -selective film to the solution phase.T he resulting voltammetric response is shown to be K + -selective,where peak position is ad irect functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
(32 reference statements)
0
38
1
1
Order By: Relevance
“…We also performed cellular localization studies in INS1E cells with the fluorescently tagged cereulide JG121 to confirmt hat the cyclic depsipeptides are cell-penetrating compounds, an important feature when studying biological eventsm ediated by K + ioni nteractions. [41][42][43] The INS1E cells, culturedu nder standardc onditions, were incubated with 2.5 and 25 ng mL À1 of the probe from an initial solution in DMSO. The nucleus of fixed cells was stained with DAPI (4',6-diamino-2-phenylindole).…”
Section: Resultsmentioning
confidence: 99%
“…We also performed cellular localization studies in INS1E cells with the fluorescently tagged cereulide JG121 to confirmt hat the cyclic depsipeptides are cell-penetrating compounds, an important feature when studying biological eventsm ediated by K + ioni nteractions. [41][42][43] The INS1E cells, culturedu nder standardc onditions, were incubated with 2.5 and 25 ng mL À1 of the probe from an initial solution in DMSO. The nucleus of fixed cells was stained with DAPI (4',6-diamino-2-phenylindole).…”
Section: Resultsmentioning
confidence: 99%
“…27,29 We have also shown that this technique can be used to release rare single cells captured on an unpatterned surface, 3 and the detection of ion release from single cells, combined with uorescence microscopy can be used to show how the cells respond to drug treatment. 30 Herein we further show it is possible to perform conventional impedance measurements on single cells that are located anywhere on the silicon electrode surface. This is achieved by illuminate the region of a single cell and monitoring changes in electrochemical impedance as the cell phenotype changes.…”
Section: Introductionmentioning
confidence: 86%
“…In order to reduce the recombination of photocarriers and improve spatial resolution, the silicon bulk can be replaced with thin silicon films (thinned silicon substrate [38,39,40], silicon on insulator (SOI) [18], amorphous silicon (a-Si) [41,42,43,44] and silicon on sapphire (SOS) [45,46]) or other semiconductor thin layers deposited on transparent substrates (GaAs [47], GaN [48], In-Ga-Zn oxide (IGZO) [49] and indium tin oxide (ITO) [50]). The sensing material such as Si 3 N 4 [1,28,38,39,51], Al 2 O 3 [52,53,54], Ta 2 O 5 [51], HfO 2 [55,56,57], NbO x [40,58,59], SnO x [60], self-assembled organic monolayer (SAM) [61,62] and nanofibers [63,64] can be used for pH sensing. Other chemical species can be also detected by modifying the sensing surface with appropriate materials.…”
Section: Measurement System Set-upmentioning
confidence: 99%